2014
DOI: 10.1128/aem.03254-13
|View full text |Cite
|
Sign up to set email alerts
|

The Legionella pneumophila Collagen-Like Protein Mediates Sedimentation, Autoaggregation, and Pathogen-Phagocyte Interactions

Abstract: iAlthough only partially understood, multicellular behavior is relatively common in bacterial pathogens. Bacterial aggregates can resist various host defenses and colonize their environment more efficiently than planktonic cells. For the waterborne pathogen Legionella pneumophila, little is known about the roles of autoaggregation or the parameters which allow cell-cell interactions to occur. Here, we determined the endogenous and exogenous factors sufficient to allow autoaggregation to take place in L. pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 70 publications
1
35
0
1
Order By: Relevance
“…The ability of bacterial cells to come into contact and form aggregates, or autoaggregation is considered important for colonization of host cells in pathogenic bacteria ( Lee et al, 2010 ; Abdel-Nour et al, 2014 ). During biofilm development, autoaggregation is a process through which a strain within the biofilm produces polymers to boost the integration of genetically identical strains, and is also a prerequisite of biofilm formation ( Zhang et al, 2004 ; Das et al, 2010 ; Nyenje et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of bacterial cells to come into contact and form aggregates, or autoaggregation is considered important for colonization of host cells in pathogenic bacteria ( Lee et al, 2010 ; Abdel-Nour et al, 2014 ). During biofilm development, autoaggregation is a process through which a strain within the biofilm produces polymers to boost the integration of genetically identical strains, and is also a prerequisite of biofilm formation ( Zhang et al, 2004 ; Das et al, 2010 ; Nyenje et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the roles of CLPs in biofilm formation are consistent with previous studies of CLPs in Streptococcus pyogenes , B . anthracis , and Legionella pneumophila [ 8 , 10 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most proteins that contain collagen-related structural motif (CSM) patterns are distributed in the Firmicutes group (including mycobacteria and Gram-positive bacteria) and in some cases a single genome encodes more than one CSM-containing protein [ 7 ]. Interestingly, some recent reports suggest that collagen-like proteins (CLPs) may play important roles in the infectious processes of some Gram-positive human pathogens, such as Bacillus anthracis , [ 8 10 ], Streptococcus [ 11 , 12 ], and Legionella pneumophila [ 13 ]. Some studies have shown that CLPs are always involved in the colonization, motility, and location processes when bacteria interact with their hosts [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, upstream biofilm members appear to influence the composition of downstream biofilms [ 36 ], and certain phenotypic features of bacteria, such as the presence of fimbriae and autoaggregation influence biofilm formation by individual members [ 37 , 38 , 39 ]. Autoaggregation by intracellular pathogens like L. pneumophila may also increase their uptake by biofilm amoebae [ 40 ], leading to a higher likelihood of selecting for virulent biofilm community members [ 41 ].…”
Section: Non-enteric Environmental (Saprozoic) Pathogens (That Caumentioning
confidence: 99%